Методика вимірювання зусилля у шнековому пресі при віджимі олії з рослинної сировини - Дідур, Володимир Аксентійович; Дидур, Владимир Аксентьевич; Didur, Volodymyr; Верещага, А. Л. (Мелітополь: ТДАТУ, 2019)
UK : В роботі описаний технологічний процес пресування мезги насіння рицини в експериментальному комплексі для віджимання олії з олійної сировини. Для контролювання величини зусилля в експериментальному комплексі використаний метод тензометрування, що полягав у розміщені на спеціальній тензобалці тензорезисторів та визначені параметрів за допомогою стенду для випробування гідроагрегатів та спеціальної експериментальної установки. RU : В работе описан технологический процесс прессования мезги семян клещевины в экспериментальном комплексе для отжимания масла из масличного сырья. Для контролирования величины усилия в экспериментальном комплексе использован метод тензометрирования, который заключался в размещении на специальной тензобалке тензорезисторов и определении параметров с помощью стенда для испытания гидроагрегатов и специальной экспериментальной установки. EN : In the production of vegetable oils, there are methods of getting oil by pressing or extraction. The solvents used to get the oil by the extraction method do not meet all the requirements using the extraction process technology. In this regard, the extraction reduces the quality indicators of oil and grist, increases the cost of the process and the harmful effects on the human body. The method of obtaining vegetable oils with the help of a press is devoid of these disadvantages. Modern instrumentation for the production of vegetable oils is associated with the use of presses of various designs, one of the technological parameters that affects the amount of oil obtained after pressing is the amount of effort developed by the press. However, mash of castor bean seeds is very different in its physicomechanical properties from other oilseeds. The force that the press develops when the mash of castor bean seeds is compressed may differ from the required value. Therefore, ensuring the technological parameters of pressing castor mash with regard to its physical and mechanical properties is an important task. Nevertheless, without perfect methods of measuring the magnitude of the force developed by the press, the solution to this problem is impossible.
Методика измерения усилия в шнековом прессе при отжиме масла из масличного сырья
Method of measuring the force in a screw press during pressing oil from vegetable raw materials
Keywords: насіння рицини; рушанка; мезга; пресування; тензорезистор; зусилля; тиск; прес; експериментальний комплекс